2019
DOI: 10.6001/actamedica.v26i1.3951
|View full text |Cite
|
Sign up to set email alerts
|

Values of circulating molecular biomarkers (microRNAs) for the evaluation of renal failure during urgent abdominal sepsis anaesthesia

Abstract: Background. Micro-ribonucleic acids (miRNAs) are small non-coding molecules important for gene regulation and management of physiological processes (1). Alterations in the expression of miRNAs are potential novel biomarkers for many diseases (2).Materials and methods. Random patients who underwent emergency surgery for abdominal sepsis were enrolled into the study (N = 27). Patients were divided into three groups according to the renal function and into two groups depending on the presence or the absence of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, several issues should be investigated before their use in clinical practice (65)(66)(67). miRNA detection is convenient and fast and its clinical diagnostic and prognostic value for patients with sepsis and related complications has gained increasing attention (68,69). The complex pathogenesis and diagnostic value of miRNAs in sepsis need to be further explored, as the identification of specific miRNAs will help to further clarify the pathogenesis of the disease and provide a way to screen novel clinical diagnostic indicators or explore molecular targeted therapies (70).…”
Section: Discussionmentioning
confidence: 99%
“…However, several issues should be investigated before their use in clinical practice (65)(66)(67). miRNA detection is convenient and fast and its clinical diagnostic and prognostic value for patients with sepsis and related complications has gained increasing attention (68,69). The complex pathogenesis and diagnostic value of miRNAs in sepsis need to be further explored, as the identification of specific miRNAs will help to further clarify the pathogenesis of the disease and provide a way to screen novel clinical diagnostic indicators or explore molecular targeted therapies (70).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that multiple miRNAs play important roles in the development of the nervous system, as well as the functional and pathological processes, which has been shown to be abnormally expressed during anesthesia (18)(19)(20), including the miR-320a family (21). Moreover, the miR-320a family has been predicted to be the upstream regulatory genes of NGB.…”
Section: Introductionmentioning
confidence: 99%